Characteristics of good quality pharmaceutical services common to community pharmacies and dispensing general practices. (1st March 2016) - Grey, Elisabeth; Harris, Michael; Rodham, Karen; Weiss, Marjorie C.
Abstract: Background: In the United Kingdom, pharmaceutical services can be delivered by both community pharmacies (CPs) and dispensing doctor practices (DPs). Both must adhere to minimum standards set out in NHS regulations; however, no common framework exists to guide quality improvement. Previous phases of this research had developed a set of characteristics indicative of good pharmaceutical service provision. Objective: To ask key stakeholders to confirm, and rank the importance of, a set of characteristics of good pharmaceutical service provision. Methods: A two‐round Delphi‐type survey was conducted in south‐west England and was sent to participants representing three stakeholder groups: DPs, CPs and patients/lay members. Participants were asked to confirm, and rank, the importance of these characteristics as representing good quality pharmaceutical services. Key Findings: Thirty people were sent the first round survey; 22 participants completed both rounds. Median ratings for the 23 characteristics showed that all were seen to represent important aspects of pharmaceutical service provision. Participants' comments highlighted potential problems with the practicality of the characteristics. Characteristics relating to patient safety were deemed to be the most important and those relating to public health the least important. Conclusions: A set of 23 characteristics for providing good pharmaceutical services in CPs and DPs was developed and attained approval from a sample of stakeholders. With further testing and wider discussion, it is hoped that the characteristics will form the basis of a quality improvement tool for CPs and DPs.